Эволюционный алгоритм поиска знаний в базах данных при создании информационных систем - Левыкин, В. М.; Чалый, С. Ф. (My University, 2001)
Розглянуто питання інтелектуального пошуку знань в масивах даних і особливості використання еволюціоннихметодов при пошуку знань. Наведено алгоритм пошуку знань в БД, що використовує еволюційні методи і дозволяє сформувати модель пошуку закономірностей в заданій предметній області. The problems of intellectual search for knowledge in data sets and features of using evolutionary methods in the search for knowledge are considered. An algorithm for searching knowledge in the database is used, which uses evolutionary methods and makes it possible to form a model for finding regularities in a given domain.
Keywords: алгоритм поиска знаний; эволюционный алгоритм; интеллектуальный поиск